KEBERLANGSUNGAN PENDIDIKAN PADA MASA PANDEMI COVID-19 DI MTS TINOMBALA PROVINSI SULAWESI TENGAH - Eko Budiywono; Muhammad Burhanudin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The objectives set out in this study are: (1) To determine the continuity of education at MTs Tinombal in the midst of the Covid-19 pandemic, (2) To determine the advantages and disadvantages of online learning at MTs Tinombala in the midst of the Covid-19 pandemic and (3) To find out the strategies used by MTs Tinombala in implementing learning in the midst of the Covid-19 pandemic so that student learning can run optimally. This study used a qualitative descriptive study conducted at MTs Tinombla, Central Sulawesi. From the results of this study, the sustainability of education at MTs Tinombala went well by combining online and offline learning methods, online activities were carried out through the WA group between teachers and students while offline was carried out by the arrival of students to school to take the learning module. The advantages of online learning at MTs Tinombala are very diverse, but to overcome these obstacles schools have not been able to overcome all the obstacles because of many factors that influence it.